ECG as a first step in the detection of left ventricular systolic dysfunction in the elderly. (30th October 2015) - Olesen, Line Lisbeth; Andersen, Andreas
Abstract: Aims: Due to the demographic development there is an increasing number of senior citizens with left ventricular systolic dysfunction (LVSD), defined as ejection fraction (EF) < 40%. Unfortunately there are under‐diagnosis and under‐treatment in the elderly of this serious condition. Echocardiography is the gold standard to diagnose LVSD, but access is limited. Simple screening methods may ensure reduction of undetected cases, and this study investigates if electrocardiogram (ECG) can be used to screen for LVSD in the geriatric population. Methods and results: A total of 260 persons aged 75 to 92 years had an echocardiography, a 12 leads ECG, and NT‐proBNP; 61 had EF < 40%, and of these 60 had an abnormal ECG. EF < 40% was significantly related to atrial fibrillation (A), pacing (P), LBBB (L), Q‐waves (Q), and QRS duration ≥ 120 ms (D). EF < 40%, atrial fibrillation, pacing, and LBBB were related to NT‐proBNP > 35 pmol/L. When APL was absent, NT‐proBNP had discriminatory value regarding LVSD in the presence of Q‐waves or QRS duration > 120 ms. Algorithms to screen for LVSD had sensitivity >90% and specificity >80% and claimed at least one of five (A/P/L/Q/D), one of 4 (A/P/L/Q), or one of three (A/Q/D) ECG changes. The optimal algorithm to reduce the need for diagnostic echocardiographies included four (A/P/L/Q) ECG changes and measurement of NT‐proBNP when Q‐waves were the only ECG change present. Conclusions: Ninety percent of LVSD may be detected, and when there is atrial fibrillation, pacing or LBBB, or QRS ≥ 120 ms/Q‐waves and NT‐proBNP>35 pmol/L, a diagnostic echocardiography should be considered.